2009
DOI: 10.1590/s1806-37132009000300009
|View full text |Cite
|
Sign up to set email alerts
|

Correlação entre parâmetros clínicos e qualidade de vida relacionada à saúde em mulheres com DPOC

Abstract: Objective: To correlate health-related quality of life (HRQL) of women with COPD with clinical parameters and with the six-minute walk distance (6MWD; six-minute walk test). Methods: Cross-sectional study involving 30 female patients diagnosed with mild or moderate COPD treated at the Respiratory Outpatient Clinic of the Presidente Dutra University Hospital. Patients completed the Saint George's Respiratory Questionnaire (SGRQ) and were evaluated in terms of respiratory pressures, spirometry parameters and 6MW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 20 publications
(18 reference statements)
0
11
0
1
Order By: Relevance
“…23 studies related to subjective fatigue were retrieved in full text and 12 were included in this section, all related to COPD [148][149][150][151][152][153][154][155][156][157][158][159].…”
Section: Dyspnoeamentioning
confidence: 99%
See 1 more Smart Citation
“…23 studies related to subjective fatigue were retrieved in full text and 12 were included in this section, all related to COPD [148][149][150][151][152][153][154][155][156][157][158][159].…”
Section: Dyspnoeamentioning
confidence: 99%
“…Dimensions of subjective fatigue have been related to pulmonary function, skeletal muscle force and quality of life in COPD patients [154,155]. Subjective fatigue measured during the 6MWT using the Borg exertion scale is associated with lower 6MWT, slower gait speed, more severe lung disease, more dyspnoea on exertion and lower HRQoL (table S27) [148,[156][157][158]. Although there are fewer SAOUTI [131] LEE [135] PACIOCCO [130] MIYAMOTO [43] BENZA [133] NICKEL [136] TUPPIN [140] data available to assess the impact of subjective fatigue during 6MWT compared with dyspnoea, existing studies support its role as an important contributor to 6MWD and disease status in COPD.…”
Section: Dyspnoeamentioning
confidence: 99%
“…(6) Studies of health-related quality of life (HRQoL) in patients with COPD with varying degrees of severity have consistently shown that these patients have significant decrements in HRQoL. (7,8) Therefore, HRQoL is an important clinical outcome in COPD.…”
Section: Introductionmentioning
confidence: 99%
“…According to these authors, this may indicate that patients with better scores the walk test have their activities less restricted and experience less impact of the disease on their daily lives. Mangueira et al (29) also found a negative correlation (r = -0.3677) between the distance covered in the 6-MWT and the "total" SGRQ score in women with COPD. Dourado et al (30) also found a negative correlation with the domains of "Activities" (r = -0.58) and "Impacts" (r = -0.63).…”
Section: (Conclusion)mentioning
confidence: 88%